Ten-year outcome of different treatment modalities for squamous cell carcinoma of oral cavity - Imjai Chitapanarux (2018)
Objective: This study reports outcomes of squamous cell carcinoma of oral cavity (SCCOC) patients with different treatment modalities. Materials and Methods: We evaluated the treatment outcomes of 775 newly diagnosed SCCOC patients treated in our hospital between 2001 and 2010. Outcome data were obtained from the medical records. Survival rates were estimated by the Kaplan-Meyer method. Cox-proportional-hazard regression models were used to compare the risk of death among all risk factors. Results: The patients were divided into group 1) surgery ± adjuvant radiotherapy (RT) (n = 323) or group 2) RT ± chemotherapy (CT) for curative intent (n = 315) or group 3) RT/CT for palliative intent (n = 137). The overall 10-year survival rate was 17%. Statistically significant difference was noted in 10-year overall survival when SCCOC was managed surgically as compared to curative RT and palliative RT/CT with 25.3 %, 12.9%, 4.7%, respectively. The hazard ratio of cancer death in group 1 was 2.0 (95% CI 1.7-2.4) as compared to group 2. Conclusion: This study suggested that surgery must be the mainstay of treatment in locally advanced stage SCCOC. Palliative RT/CT still offered long term survival in some SCCOC patients.